The Domestic Political Intersections of the South African Community’s “Expression of Solidarity” with the Hungarian Refugee Crisis, 1956–1957 - Snyders, Hendrik (Journal of Central and Eastern European African Studies, 2024)
The violent repression of the Hungarian revolution by the Soviet military forces during October-November 1956 turned four per cent (4%) of the national population into refugees needing social relief from distress and a new home. While some countries condemned Soviet aggression and refused recognition to the successor government installed by the occupational forces, others rendered a mass assistance program and granted temporary and permanent asylum to the victims. The Union of South Africa, fiercely anti-communist in its orientation, actively participated and fully supported the international relief effort, supposedly as an expression of its commitment to human rights, freedom, and democracy. South Africa offered, among other things, financial support, and an alternative home to 1,300 refugees. This was achieved through the national mobilisation of the white community, inclusive of state departments, local branches of the International Red Cross, welfare organisations, universities, cultural groups, individuals, expatriate groups, municipalities and churches. On the other hand, black people’s woes were largely ignored; they were excluded from such initiatives. Indeed, the Hungarian resettlement project took place against the background of increased anti-apartheid protest and repression and events such as the treason trial of several political activists and the Alexandra bus boycott. This duality earned the country both criticism and praise.